CONSTRUCTION OF SHARIA GOOD CORPORATE GOVERNANCE MODEL AT BPRS BUMI RINJANI PROBOLINGGO INDONESIA - Amani, Tatik; Roziq, Ahmad; Sulistiyo, Agung Budi (International Journal of Social Science and Business, 2017)
These research objectives are to compose of construction of sharia good corporate governance model at BPRS Bumi Rinjani Probolinggo. The study use case study approach with using methods of survey and exploratory. Techniques of data analysis use Miles & Huberman The result of the research shows that the written report of the implementation of governance in BPRS Bumi Rinjani Probolinggo has not been done yet. According to POJK No. 30 / POJK.05 / 2014 that the finance company is obliged to make a writing report, so we must make aÂ  sharia governance model and report in BPRS Bumi Rinjani. The elements were included in the governance model are to add two principles of governance: integrity and social awareness, so that governance becomes seven (out of five set by law and two elements was get in) that istransparency, accountability, responsibility, independency, fairness, integrity and social awareness. To support the effectiveness of Dekoms tasks are included elements of the establishment of Audit Committee, Risk Monitoring Committee and Remuneration Committee. In order to an implementation of good governance was good, it is implanted to the whole range for implementation of Shariah governance that all transactions and BPRS Bumi Rinjani operations do not contain usury, maysir and gharar.Keywords : Sharia, Compliance, Governance, Integrity, Social Awareness, BPRS